Commissioning of optical surface imaging systems for cranial frameless stereotactic radiosurgery. Issue 5 (29th March 2021) - Zhang, Lei; Vijayan, Sarath; Huang, Sheng; Song, Yulin; Li, Tianfang; Li, Xiang; Hipp, Elizabeth; Chan, Maria F.; Kuo, Hsiang‐Chi; Tang, Xiaoli; Tang, Grace; Lim, Seng Boh; et al.
Abstract: Purpose: This study aimed to evaluate and compare different system calibration methods from a large cohort of systems to establish a commissioning procedure for surface‐guided frameless cranial stereotactic radiosurgery (SRS) with intrafractional motion monitoring and gating. Using optical surface imaging (OSI) to guide non‐coplanar SRS treatments, the determination of OSI couch‐angle dependency, baseline drift, and gated‐delivered‐dose equivalency are essential. Methods: Eleven trained physicists evaluated 17 OSI systems at nine clinical centers within our institution. Three calibration methods were examined, including 1‐level (2D), 2‐level plate (3D) calibration for both surface image reconstruction and isocenter determination, and cube phantom calibration to assess OSI‐megavoltage (MV) isocenter concordance. After each calibration, a couch‐angle dependency error was measured as the maximum registration error within the couch rotation range. A head phantom was immobilized on the treatment couch and the isocenter was set in the middle of the brain, marked with the room lasers. An on‐site reference image was acquired at couch zero, the facial region of interest (ROI) was defined, and static verification images were captured every 10° for 0°–90° and 360°–270°. The baseline drift was assessed with real‐time monitoring of the motionless phantom over 20 min. The gated‐delivered‐dose equivalency was assessed using the electron portal imaging device and gamma test (1%/1mm) in reference to non‐gated delivery. Results: The maximum couch‐angle dependency error occurs in longitudinal and lateral directions and is reduced significantly ( P < 0.05) from 1‐level (1.3 ± 0.4 mm) to 2‐level (0.8 ± 0.3 mm) calibration. The MV cube calibration does not further reduce the couch‐angle dependency error (0.8 ± 0.2 mm) on average. The baseline drift error plateaus at 0.3 ± 0.1 mm after 10 min. The gated‐delivered‐dose equivalency has a >98% gamma‐test passing rate. Conclusion: A commissioning method is recommended using the 3D plate calibration, which is verified by radiation isocenter and validated with couch‐angle dependency, baseline drift, and gated‐delivered‐dose equivalency tests. This method characterizes OSI uncertainties, ensuring motion‐monitoring accuracy for SRS treatments.